(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
Corruption is a problem that can have an impact on Indonesia’s development both in terms of the economy, education and even the government system. The aim of this research is to contribute to the understanding and improvement of law enforcement actions related to corruption at the local level. This study used qualitative research methods. The data for this research was obtained through observation, interviews, documentation. To get an accurate analysis of the results of this research, use Nvivo 12 Plus Software. The research results show that the strategy for handling corruption cases by the Makassar City Police includes an approach that involves system improvements, education and repressive measures. The main focus is to supervise strategic projects, increase public understanding, and encourage participation and law enforcement with the principles of transparency and integrity. The overall strategy aims to effectively handle and prevent corruption cases in Makassar City.